Salud y sexualidad en la población juvenil del departamento de Caldas - Vélez Álvarez, Consuelo; Vidarte Claros, José Armando (Universidad y Salud, 2023)
This work is part of the results of the macro-project “Characterization of Juvenile Human Development in Caldas Colombia” in the area of Health and Sexuality. Objective: To recognize the characteristics of health and sexuality of young people in Caldas. Methods: The area presented (health and sexuality) was quantitative with youth population of 237,130 in Caldas Department, the sample was of 4,479 young people with a sampling design (simple random). Results: There is difference in gender regarding health condition, 91.6% of men reported a positive response, and in women was 87.6%. The chi-square showed dependence between these variables p <0.000. The identified health problems were smoking and not practicing sports, respiratory problems, stress, depression and heart problems. The registration in health services showed a gender difference, being higher in women, there is dependence between these variables, p 0.004. The sex ratio compared to having had sexual intercourse was 75.5% versus 74.8% in men and women. The average age of first intercourse was 15.6 years old. 38.9% used a contraceptive method at first intercourse. Conclusion: There are gender differences for categories such as health status, use of family planning methods, people who they had first and last intercourse with, and abortion.